Serum prostate-specific antigen as a predictor of prostate volume in Sudanese patients with benign prostatic hyperplasia - Alawad, Awad; Younis, Faisal; Eltoum, Abdalla Mahgoub; Abdelgani, Sana Azmi (International Journal of Medicine, 2014)
Background: Benign prostatic hyperplasia (BPH) is now recognized as one of the principal medical problems facing the male population in Sudan. Objective: The aim of this study is to assess the ability of serum prostate-specific antigen (PSA) to predict prostate volume (PV) in patients with benign prostatic hyperplasia (BPH). Materials and Methods: This is retrospective observational case-detection hospital based study. Eighty medical records of patients with an enlarged prostate attending the urology clinic at University Teaching Hospital were enrolled. This research was conducted in University Charity Teaching Hospital, Khartoum, Sudan. Results: Enrolled patients had a median age of 63.5 years (51 to 94), a mean PSA of 2.94 ng/ mL and a mean PV of 46.96 mL, respectively. There is linear relationship between PSA levels and prostate size. Those with a prostate size of > 40 ml were found to be more likely to have high PSA mean level. PSA mean values were found to be associated with age (P <0.006). Conclusion: Serum prostate specific antigen (PSA) is significantly correlated with prostate volume in Sudanese men. PSA may be a useful tool in making therapeutic decisions and follow-up management in BPH patients. Keywords: Serum Prostate Specific Antigen; Prostate Volume; Benign Prostatic Hyperplasia.